Hierarchical Tubular Structures Composed of Co3O4 Hollow Nanoparticles and Carbon Nanotubes for Lithium Storage - Chen, Yu Ming (2016)
Hierarchical tubular structures composed of Co3O4 hollow nanoparticles and carbon nanotubes (CNTs) have been synthesized by an efficient multi-step route. Starting from polymer-cobalt acetate (Co(Ac)2) composite nanofibers, uniform polymer-Co(Ac)2@zeolitic imidazolate framework-67 (ZIF-67) core–shell nanofibers are first synthesized via partial phase transformation with 2-methylimidazole in ethanol. After the selective dissolution of polymer-Co(Ac)2 cores, the resulting ZIF-67 tubular structures can be converted into hierarchical CNTs/Co-carbon hybrids by annealing in Ar/H2 atmosphere. Finally, the hierarchical CNT/Co3O4 microtubes are obtained by a subsequent thermal treatment in air. Impressively, the as-prepared nanocomposite delivers a high reversible capacity of 1281 mAh g−1 at 0.1 A g−1 with exceptional rate capability and long cycle life over 200 cycles as an anode material for lithium-ion batteries.